THE CRIMINAL LAW POLICY IN CASES OF CRIMINAL INFRINGEMENT MADE BY POLRI (POLICE OF REPUBLIC OF INDONESIA) MEMBERS (STUDY IN REGIONAL POLICE IN CENTRAL JAVA) - Anggie Andhika A. Putri Lihu (IJCLS (Indonesian Journal of Criminal Law Studies), 2018)
The Police of the Republic of Indonesia (Polri) has a role to realize the internal security of Indonesia. Many people consider that members of the Police who commit a criminal offense will not be prosecuted under the law as they should, and get protection from the Police institution itself. This study aims to determine the extent of criminal law policy in an effort to overcome criminal acts committed members of the Police either formulatively, applicative or executive. This research uses normative juridical method with empirical juridical approach to make this research more weighted. Normative juridical method is used to examine and analyze formulative policies related to criminal acts committed by Polri members, while empirical juridical approach is used to examine law enforcement practices against members of the Police who committed criminal acts in the territory of Regional Police of Central Java. The results of the study indicate that binding regulations for Indonesian citizens who commit criminal offenses both regulated in the Criminal Code of Indonesia and outside the Criminal Code of Indonesia, are also binding on the members of the Police who commit the crime. While the future criminal law policy regarding criminal acts committed by members of the Police has improved, although there are still some weaknesses that still need to be reviewed, in addition, also investigated the practice of criminal law enforcement against members of the Police who committed criminal acts. The results of this study attempt to straighten the view of the people of Indonesia who assume that every member of the Police who commit a criminal act will be protected by the Police institution itself.